Pengaruh Latihan Lari Zig-Zag Terhadap Kecepatan Menggiring Bola Pada Siswa Sdn Betek Taman 03 Probolinggo - Hermawan Diva Ardi Wijaya (Unimuda Sport Journal : Jurnal Pendidikan Jasmani, 2024)
This study aims to examine the effect of zig-zag running training on the dribbling speed of students at SDN Betek Taman 03 Probolinggo. The research used an experimental design with a One Group Pretest-Posttest Approach. Fourteen 6th-grade students were purposively sampled to participate in zig-zag training for 16 sessions over two months, with a frequency of three times a week. Data were collected through dribbling tests before and after the intervention, showing a significant increase in students' dribbling speed from an average of 15.67 seconds before training to 12.822 seconds after training. Statistical analysis indicated that the zig-zag training method was more effective than the shuttle run in improving dribbling speed, with a difference of 0.403 seconds in improvement. These findings are supported by previous research, showing that varied and dynamic zig-zag training not only enhances speed but also agility and ball control. This study recommends adopting zig-zag training in school soccer programs to optimize the development of students' dribbling skills.